Postoperative morbidity and histopathologic characteristics of tonsillar tissue Following coblation tonsillectomy in children : a prospective randomized single-blind study - Roje, Željka, 1967- (Array, 2009)
Abstract: The aim of this prospective randomized single blind study was to determine the depth of thermal damage to tonsillar tissue due to coblation, and to compare it with thermal damage to tonsillar tissue following conventional tonsillectomy; to correlate the depth of thermal damage to tonsillar tissue with the parameters of postoperative morbidity, to compare intraoperative blood loss, postoperative pain severity, time to resuming normal physical activity, and incidence of postoperative bleeding between two groups of tonsillectomized children aged up to 16 years. 72 children aged 3–16 years scheduled for tonsillectomy randomly assigned into two groups submitted either to conventional tonsillectomy with bipolar diathermy coagulation or to coblation tonsillectomy, with a 14-day follow up.Statistically significant differences were observed in the depth of thermal damage to tonsillar tissue (p<0.001), intraoperative blood loss (p<0.004), in postoperative pain severity (p<0.05) and in time to resuming normal physical activity between the two groups (p<0.001). There was no case of reactionary or secondary bleeding in either group. In this paper for the first time we have correlated postoperative morbidity and thermal tissue damage: less thermal damage is associated with less postoperative morbidity